THE ELDERLY’S QUALITY of LIFE IN THE PANTI WERDHA AND THE COMMUNITY OF BANDUNG CITY: WHOQOL-BREF and WHOQOL-OLD Indonesian Version - Nadya Ayudiawati Nurbasari; Sharon Gondodiputro; Lazuardhi Dwipa (Universitas Padjadjaran, 2019)
The inability of families to care for their elderly causes them to place the elderly in the Panti Werdhas. The elderly who move to a Panti Werdha usually have difficulties to adapt the new surroundings that can affect their quality of life. The World Health Organization (WHO) developed instruments to measure quality of life, a multidimensional and cross-cultural approach, namely WHO Quality of Life-BREF (WHOQOL-BREF) and WHO Quality of Life-OLD (WHOQOL-OLD). Both instruments have been translated into Indonesian language. The aim of the study was to analyze the differences in quality of life between the elderly who live in the Panti Werdhas and in the community. A cross-sectional analytic quantitative study was carried out from October to November 2019 at 5 Panti Werdhas and 6 public health centers (Puskesmas) in Bandung City, West Java, Indonesia. The total number of respondents in the Panti Werdha and at the Puskesmas as many as 42 respondents. The selection of respondents in the Panti Werdhas used purposive sampling, whereas in the puskesmas used consecutive sampling. The Chi-square or Fisher's Exact test was used to analyze the respondent's characteristics and the Mann-Whitney test was used to analyze differences in the quality of life. This study discovered that respondents living in the Panti Werdhas were older, not married/divorced and less educated compared to respondents in the community. The quality of life of the elderly in Panti Werdhas was lower compared to the elderly in the community for all dimensions (p=≤0.05) except the dimensions of death and dying (p=0.741). It can be concluded that there are differences in the quality of life between the elderly who live in Panti Werdhas and in the community except at the dimensions of death and dying.